Peculiarities of stress-strain state of the conical stem of the hip endoprosthesis in different types of its fixation - Loskutov, Oleg (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2015)
Objective: To study stress state of the femur and the conical femoral stem of the hip endoprosthesis KS «ORTEN» in different types of fixation and functional loadings. Methods: The finite element modeling with using the software complex «ANSYS» and computational model «bone – implant». Results: it was found that regardless of level of fixation maximal tensile stresses arise on the lateral surface of the femoral stem and bone, and squeezing ones were on the medial surface. In cases of diaphyseal fixation type we determined maximal stresses in the endoprosthesis when the surface area of contact with the bone is too small (less than 40 %). Increasing the contact area of the femoral stem with the bone increases the rigidity of the system «bone - implant» and reduces tensile and compressive stresses in the body of the femoral stem. In case of diaphyseal fixation there can occur stress concentration in the distal femur leading to the risk of stress-shielding effect and instability of the implant. In case of metaphyseal fixation we revealed a uniform distribution of stress on the bone which eliminates excessive concentration of mechanical stress. Optimal stress distribution in the femur may be achieved in case when the contact area of the femoral stem with the bone is 50 % or more. Conclusion: The value of the maximum stresses in the conical femoral stem of KS «ORTEN» with metaphyseal-diaphyseal type of fixation was 34 ÷ 140 MPa, and for the femur was 5,8 ÷ 7,15 MPa. For all types of fixation of the endoprosthesis maximal tensile stresses were found on the lateral surface of its stem and squeezing ones on the medial. In case of diaphyseal fixation of the conical femur stem stress concentration occurs in the distal femur which increases the risk of stress-shielding effect and instability of the endoprosthesis. In cases of metaphyseal and metaphyseal-diaphyseal fixation stresses distribute evenly ensuring continued functioning of the endoprosthesis.